The cardiac anoxemia test - Peñaloza Ramella, Dante (1951)
It is well known the fundamental importance of the accurate diagnosis of Angina syndrome. According to White, this dindrome constitutes 11.8% of heart disease, demonstrating that it is not that uncommon, especially in recent decades. It is well known, also, the relatively poor prognosis of angina; White on statistics, the average life, after the first attack, only reaches 9.1 years. Finally, it is known that an essential part of preventive treatment of attacks of angina pectoris, is the radical change in lifestyle, which may result, in many cases, very serious consequences for the patient, from the point of view economic and social. This sort of treatment that would interfere primarily in the patient's life and prognosis, as we have said, is relative severity, can only be justified on the basis of a definite diagnosis of the syndrome of angina pectoris.